Reconfiguring Identity through the Influence of English in Students at UNA’s Campus in Sarapiquí - Viales Angulo, Jairo Eduardo (2016)
This research took place in Universidad Nacional (UNA), Sarapiquí Campus and it proposes to find out how students at CUNLIMON deal with daily life activities into the English classroom in order to define their identity while interacting with others. As stated by Whorf (1997) “…People act about situations in ways which are like the ways they talk about them” (p.453). Identity, in other words takes place because these people do not know who they are. People see, perceive, and make sense of them and each other based on what the society wants them to see. This is called according to Isaacs as the perception of each other (p.48). The problem emerged in this research has been derived from the perspective students have from them as individual and as part of a group in order to identify what factors intervene to direct students create their own individual and group identity. Finally, it is mandatory to figure out the ways in which communication in English contributes to reconfigure the individual and group identity of those students enrolled in the English as a Foreign Language Major offered at UNA’s campus in Sarapiquí.Additionally, these learners will identify each other with the Caribbean culture. Students will realize that the Costa Ricans’ English culture emerged mainly from people who use to lived and actually live in Limon.